Ship Communication System Planning Analysis Using Very Small Aperture Terminal (VSAT) Single Channel Per Carrier (SCPC) With KU-Band Frequency - Susilo, Susilo; Pardomuan, Remon; Widodo, Bambang (Prodi Teknik Elektro FT UKI, 2021)
For commercial frequency telecommunication purposes, commonly used are C, Ku, and Ka-band. C-band is the most popular frequency used in Indonesia; its low frequency makes it relatively more resistant to rain interference. However, the use of C-band frequency is no longer sufficient for future communication needs. Alternative solution with higher frequency usage than C-band and Ku-band. The advantage of Ku-Band frequency is that with smaller antennas can produce large bandwidth (broadband), The use of Ku-band frequency also avoids interference because it is relatively uncommon in terrestrial systems. Determination of satellite, concerning the type of satellite, coverage area (footprint), and availability of satellite links (C-Band or Ku-Band). In this thesis, the satellites used in data analysis are SES-9 satellites, which are on a 108 ° East orbit with the availability of Ku-Band 81 links. (C / N) Total_inroute and (C / N) Total_outroute for the analyzed links are 11.49 dB and 12.44 dB, respectively. This value is greater than the value (C / N) req of 10.22 dB (C / N)> (C / N) req. ship communication system using VSAT SCPC with Ku-Band frequency can be applied